(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
With the rapid growth of e-commerce, governmental and corporate agencies are taking extra precautions when it comes to protecting information. The development of e-security as a discipline has enabled organisations to discover a wider array of similarities between attacks occurring across their security environment and develop appropriate countermeasures. To further improve the security of information, there is a need for conceptualising the interrelationships between e-security and the major elements involved in changing a company’s infrastructure. Organisations should act in an ethical manner, especially when it comes to e-security and e-privacy policies, procedures, and practices. The consequential theory of utilitarianism is used and applied to a conceptual model to help explain how organisations may develop better secured information in an information-sharing and globally networked environment. E-security is a critical concern for both consumers and business. Establishing trust between all parties in an online transaction is vital for the success of e-commerce. The public wantsÂ full assurance that the information they supply is going to the company they think it is going to, will not be misused by that company, and that credit card information or other payment mechanisms are confidential and secure. On the other hand, companies also want that their systems must remain protected from intruders and they cannot tamper with the data. Some degree of risk is always associated with E-transactions, if security controls are not applied while engaging into such transactions. Users must be sure before engaging into transactions that they are safe and the information provided by them is not going to unauthorized people. Cyber crimes can involve criminal activities that are traditional in nature, such as theft, fraud, forgery, defamation and mischief, all of which are subject to the Indian Penal Code. The abuse of computers has also given birth to a gamut of new age crimes that are addressed by the Information Technology Act, 2000. In this paper, I have covered the e-security issues such as elements of e-security, security threats or cyber crimes, tools for e-security, precautions for secure e-commerce and various studies regarding e-security issues.